Anthropometric Characteristics of Volleyball Players with respect to Playing Positions: In Ethiopian Female Premier League - Berhanie Asrat Bekele; Alemmebrat Kiflu Adane; Teketel Abreham Kabiso (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2022)
The aim of this study was to investigate the anthropometric characteristics of Ethiopian female premier league volleyball players in relation to playing positions. The study encompassed 42 female premier league volleyball players (age: 25.60+6.4 years). The players were categorized on the bases of playing position: including: -setters (n=5), middle blockers (n=7), outside-hitters (n=11), opposite hitters (n=11), and liberos (n=8). Anthropometric measurements such as: five basic, six body lengths, six body circumferences, and five skinfolds were assessed. Descriptive statistics and One-Way ANOVA were used to identify the differences among the anthropometric characteristics of the players' at different playing positions. Significant mean differences were separated using the Tukey B a,b mean difference test at P < 0.05.The result revealed that there were significant differences in standing height, sitting height, standing reach height, arm and leg lengths among female volleyball players in different playing positions. However, the differences in weight, BMI, body circumferences, and skinfolds were not significant. Up on the results, it was possible to conclude that players' anthropometry is among the factors that affect success in a game. Considering players' anthropometry seems to be crucial at the time of selection and assigning of players to playing positions.